MODEL PENYELESAIAN TINDAK PIDANA RINGAN MENURUT HUKUM ADAT DI MASYARAKAT MINANGKABAU - Widiadara, Kandi; Putri, Riska; Wanda, Wanda (PARENTAL, 2013)
The light criminal case occurring in Indonesia required a legal breakthrough to solve. The emphasis on local wisdom in coping with light criminal case becomes one form of progressive law. The advantage of progressive law with the existence of local wisdom in each customary area resulted in the solution to the light crime occurring in Indonesia. The light crime handling was carried out based on local wisdom in Minangkabau people could be done in Peradilan Nagari (First Instance Court), in this case, by Kerapatan Adat Nagari (District Customary Meeting) (KAN).